2018
DOI: 10.1155/2018/1290179
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Antioxidant Systems in Inflammatory Bowel Disease

Abstract: The global incidence of inflammatory bowel disease (IBD), a group of chronic gastrointestinal disorders, has been rising. The preponderance of evidence demonstrates that oxidative stress (OS) performs a critical function in the onset of IBD and the manner of its development. The purpose of this review is to outline the generation of reactive oxygen species and antioxidant defense mechanisms in the gastrointestinal tract and the role played by OS in marking the onset and development of IBD. Furthermore, the rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 53 publications
0
71
0
2
Order By: Relevance
“…In particular, intestinal epithelial cells (IECs) can sense and respond to microbial stimuli to reiforce the barrier function and to participate in the coordination of an appropriate immune response. 7 Thus, the control of the inflammation and the oxidative stress has a primary role in the IBDs treatment. 3 The main factors involved in the inflammatory cascade during IBDs are cytokines (eg, tumor necrosis factor-α, TNF-α; interferon-γ, IFN-γ; interleukin-6, IL-6), which are also linked to nuclear factor-κB (NF-κB) activation, chemokines, adhesion molecules, and reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, intestinal epithelial cells (IECs) can sense and respond to microbial stimuli to reiforce the barrier function and to participate in the coordination of an appropriate immune response. 7 Thus, the control of the inflammation and the oxidative stress has a primary role in the IBDs treatment. 3 The main factors involved in the inflammatory cascade during IBDs are cytokines (eg, tumor necrosis factor-α, TNF-α; interferon-γ, IFN-γ; interleukin-6, IL-6), which are also linked to nuclear factor-κB (NF-κB) activation, chemokines, adhesion molecules, and reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we did not evaluate oxidative stress nor expression of antioxidant enzymes. However, as increasing evidence suggested that DSS creates oxidative stress in mice [ 57 ] and induces pro-inflammatory cytokines [ 58 ]; thus, antioxidants are suggested to be used to treat IBD [ 59 ]. Moreover, a number of studies have reported that antioxidants alter cytokine production [ 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…During experimental colitis, the oxidants play a critical role in the inflammatory reaction by increasing the number of neutrophils and macrophages that induce a self-sustaining loop (Kurutas, Cetinkaya, Bulbuloglu, & Kantarceken, 2005;van der Veen, de Winther, & Heeringa, 2009). Endogenous antioxidants degrade highly reactive oxygen species (ROS), thus become important targets for IBD treatment (Guan & Lan, 2018). Herein, we detected lipid peroxide (i.e.…”
Section: Discussionmentioning
confidence: 93%